Pengembangan E-Majinatif pada Materi Sistem Pencernaan Manusia Untuk Menumbuhkan Motivasi Belajar Siswa SMP - Gita Fitri; Dwi Indah Suryani; Annisa Novianti Taufik (PendIPA Journal of Science Education, 2026)
Low student motivation in science learning, influenced by the inappropriate selection of learning methods and limited teaching materials that are unable to facilitate active student involvement in the science learning process, forms the basis for this study. This study aims to develop valid and usable E-Majinatif digital teaching materials on the human digestive system to foster learning motivation among junior high school students. Research and Development (R&D) was used as the research method with the ADDIE model, which was limited to the development stage. The subjects in this study consisted of two subject matter experts, two teaching material experts, and three practitioners (junior high school science teachers). The research instruments used were validation questionnaires for subject matter experts, teaching material experts, and practitioners. In this study, data analysis was conducted using quantitative data in the form of numbers obtained from the research results and qualitative data in the form of suggestions and criticism from validators. The assessment results showed that the overall average percentage of the two subject matter experts, two teaching material experts, and three practitioners (junior high school science teachers) reached 94.27% and was categorized as “highly valid.” Based on these results, E-Majinatif on digestive system material is declared very suitable for use in science learning to foster learning motivation among junior high school students.